Climate Projections and Uncertainties over South America from MRI/JMA Global Model Experiments - Blazquez, Josefina (2012)
This paper analyses the climate change projected for the near and distant future in South America using MRI/JMA (Japanese Meteorological Agency) global model simulations with resolutions of 20 and 60 km. Changes in mean climate, as well as in the annual cycles and interannual variability of temperature and precipitation are discussed. An analysis is also made of the uncertainties of the 60 km resolution model experiments. For the near and distant future, both, the 20 km and 60 km resolution MRI/JMA models project that temperature changes will be positive in all seasons. The greatest values of change are over the Andes and over tropical and subtropical latitudes of the study region. In all the subregions analysed, the 20 km model projects greater changes in the annual cycle of mean temperature than the 60 km model. Changes in summer precipitation are positive over most of the continent, except for southern Chile. Autumn precipitation is projected to increase over northern Argentina and north-western South America and to decrease over central Chile in winter, which might be due to the southward shift of the Pacific storm-track. The most significant positive change in Southeastern South America (SESA) is projected to occur in spring precipitation. In general, projected changes in the annual cycle are greater in the rainy seasons of each subregion. No significant changes are expected in the interannual variability of temperature and precipitation. La Plata basin is projected to experience increased runoff, which would indicate that the projected rise in precipitation would have stronger effect than projected warming. The analysis of climate projection uncertainties revealed that temperature projections are more reliable than precipitation projections; and that uncertainty in near future simulations is greater than in simulations of the end of the century.